전신마취시 파모티딘 전처치가 위내용물의 용량과 산도에 미치는 영향 - 배성빈; Sung Bin Bae; 김현정; Hyun Jeong Kim; 염광원; Kwang Won Yum (Korean journal of anesthesiology, 2001)
Background: Severity of aspiration pneumonitis is associated with acidity and volume of aspirated gastric contents. Volume and acidity of gastric contents are influenced by food, drugs, and patient factors. However, most studies were performed without controlling these factors. The objectives of this study were to determine the effects of a 20 mg intravenous famotidine injection on gastric content volume and acidity, 1 to 2 hours prior to general anesthesia after controlling the last intake of food. Methods: One hundred twenty three healthy patients were randomly assigned to famotidine and control groups. All patients were requested to drink 200 ml of milk the night before surgery in order to control food related factors and fasting time. After induction of general anesthesia, volume and acidity of aspirated gastric contents were measured. Results: There were no significant differences in acidity of aspirated gastric contents between the two groups. However, the famotidine group showed a significant aspirated gastric volume reduction compared with that of the control group. Conclusions: Famotidine premedication by intravenous injection 1 to 2 hours prior to general anesthesia may be effective to prevent aspiration pneumonitis by reducing gastric content volume. (Korean J Anesthesiol 2001; 40: 443~447)